Technology and Entrepreneurship Combine: Shaping an Innovative Future - Putra, Yogi Irdes; Idrus, Ali; Firman, Firman (Journal of Economics Education and Entrepreneurship, 2024)
Technology's rapid development has had a significant impact on the world of entrepreneurship. The combination of technology and entrepreneurship creates a business environment full of new opportunities, innovation, and economic growth. Technological innovation has a positive effect on economic growth, especially when applied in business. This research will explore how the fusion of technology and entrepreneurship not only stimulates business transformation but also opens doors for entrepreneurs to face future challenges. The research method used is descriptive, involving analysis of published articles and case studies. The research findings reveal that the first combination of technology and entrepreneurship creates limitless opportunities for entrepreneurs to design an innovative future. Secondly, it provides deep insights into how technology development and entrepreneurship can mutually reinforce each other, creating a dynamic business ecosystem and bringing significant benefits to society as a whole. By understanding the complexity and potential of this combination, we can together create a more sustainable, inclusive, and innovative future.